DIGITAL MARKETING COMMUNICATION STRATEGY ON THE USE OF INSTAGRAM SOCIAL MEDIA BY BASO ACI GANTENG - Cahyati, Witri; Priadi, Muhammad Dadi; Putra, Dwi Kurniawan Riyadi; Irawati, Dwi Sandra (TOPLAMA, 2024)
The use of Instagram social media in implementing product promotion and sales strategies can provide significant convenience for business people. Baso Aci Ganteng uses the Instagram social media account @basoaciganteng as the main promotional media in marketing their products. The purpose of this study is to understand why Baso Aci Ganteng chose Instagram as a digital marketing communication strategy and to determine the advantages gained when using Instagram as a medium for digital marketing communication strategies. This study uses a qualitative research method approach with a case study approach.  Data collection techniques include interviews,  observations,  and documentation studies.  The research obtains data sources directly from business people,  where the key informants are the business owners themselves and other main business actors as primary data sources. Based on the results of the research, the researcher concludes that Baso Aci Ganteng practices digital marketing communication strategies online through Instagram, which connects to a wider reach of consumers and thus increases sales.